Case study: Design of an absorption refrigeration system for milk preservation in Jalisco, Mexico. (April 2023) - Saucedo-Velázquez, J.; Gutiérrez-Urueta, G.; Pacheco-Reyes, A.; Rivera, W.
Abstract: This article presents a case study focused on designing a refrigeration system for milk storage in a town of Jalisco, Mexico. An absorption refrigeration unit is proposed, activated with a geothermal heat source from an existing well. An economic analysis of the proposal and its comparison with a conventional system and a solar system is presented. The proposed system must provide refrigeration to the warehouse (cold room) with a cooling load of 5 kW, with a geothermal heat source temperature of 80 °C for the single effect system and 163 °C for the double effect system. For the design of the warehouse, the thermal loads were obtained through ceilings and walls, by lighting, infiltration, and by occupation, through the EnergyPlus software. The results show values of monthly thermal loads ranging between 0.94 and 1.1 kW. The single-effect system achieved a COP of 0.85 costing approximately $13, 083, while the double-effect system reached a COP of 1.38 with a cost of $18, 144. Highlights: A case study for milk preservation on a real farm in México is presented. Two configurations of absorption cooling systems were analyzed, driven with geothermal energy. The study includes the thermodynamic, technical, and economic study to show the system's feasibility. The double-effect system was the most efficient but expensive, reaching a COP of 1.38. Both systems showed to be technologically and economically feasible during their useful life.